Public Disclosure of Environmental Violations in the Republic of Korea - Hong, Jong Ho; Laplante, Benoit; Meisner, Craig (World Bank, Washington, DC, 2014)
Since 1989, environmental authorities of the Republic of Korea have published on a monthly basis a list of enterprises violating the country's environmental rules and regulations. This may be the longest environmental public disclosure program currently in existence. Over the period 1993-2001 in excess of 7,000 violations have been recorded in these monthly violation lists, involving more than 3,400 different companies. In this paper, the authors provide a comprehensive descriptive analysis of this dataset. Results suggest that the news media have given an important, though perhaps declining coverage, to the violation lists, with a focus on publicly traded companies, failures to operate pollution abatement equipment, and prosecutions.